Metodikstudie av trollingfisket i Vänern : Jämförelse av fångstrapportering mellan intervjuer och enkäter gjorda på trollingfiskare samt vädrets påverkan på ansträngning - Höök, David (Karlstads universitet, Fakulteten för hälsa, natur- och teknikvetenskap (from 2013), 2014)
There are five endemic populations of migratory Atlantic salmon (Salmo salar, Salmonidae) and brown trout (Salmo trutta, Salmonidae) remaining in Lake Vänern, whereof two are salmon and three are trout. There is one population of each species in Klarälven, also one of each in Gullspångsälven and there is a population of trout still remaining in Tidan River. Since the beginning of the 20th century endemic populations of salmon and trout have either vanished or declined dramatically due to the construction of hydropower in the rivers around the lake, and still today the future of the remaining populations remains uncertain. To manage salmonid fishes effectively more knowledge of their ecology throughout their different life-stages is needed. A large part of the Lake Vänern salmonoids lives are spent in the lake, where a mayor mortality factor is recreational fishing, especially angling. Estimation of fishing effort and catch is important in order to remain a sustainable fishery. In Lake Vänern commercial fishers are bound to report their catch, but anglers are not, -even though they are now thought to be responsible for the largest proportion of the catch. Angler interviews and access point surveys are the best ways to get accurate information in order to assess sport fish effort and catch. There are drawbacks of this method though that includes large costs, logistical problems and biased results due to the higher chance of interviewing the most avid anglers. To hand out mail-surveys is a kind of off-site survey that is less costly compare to interviews, but the drawbacks are bigger in getting correct information due to biased results from non-respondence. A study was conducted to compare an interview-survey with a mail-in survey, in which the interviews were conducted in Lillängshamnen, a port on the northern coast of Lake Vänern, and the mail-in surveys were distributed in different ports around the lake, though not in Lillängshamnen. This study shows a significant difference in catch per boat day between the ...